Improving service quality at universities through student journey mapping - Ludwiczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
Abstract: The aim of the pilot study was to determine whether student travel mapping can be an effective method supporting the improvement of services at a university in the context of creating value for students and their participation in creating this value. In-depth qualitative research was carried out, consisting in conducting semi-structured interviews with students. The study used the customer journey mapping (CJM) method.
Keywords: student experience; university; student journey mapping; service quality improvement